Fajar Islam Terbit Kembali di Spanyol - Didin Saefuddin (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2004)
The building of The Great Masque of Granada Spain indicates the appearing of islamic movement There, the centre of islamic culture and maslem intellectuals will be developed as well as those of centuries ago